Transporte aéreo y pandemia de la COVID-19: ¿Hacia un cambio de trayectoria en la red aeroportuaria española? - Díez-Pisonero, Roberto; Gago-García, Cándida (Revista de Estudios Andaluces, 2022)
La COVID-19 ha supuesto un profundo shock en la economía global y en particular en la industria de la aviación, al ser esta damnificada de medidas restrictivas para frenar la propagación del virus. En este trabajo además de presentar, como contexto, el impacto de la COVID-19 a escala global en el sector comercial de la aviación, se realiza un análisis de la conectividad aérea de los aeropuertos españoles para comprender los cambios acaecidos. Para el estudio, de carácter diacrónico (1970-2020), se emplea un coeficiente de conectividad topológica, cartografía y otras medidas (análisis de frecuencias y volumen de viajeros). La pandemia está suponiendo un punto de inflexión en la historia aeronáutica que obliga a una adaptación constante en España y en el resto del mundo, tanto en términos comerciales como en materia de seguridad sanitaria. Unlike other previous crises (Gulf wars, 9/11 terrorist attacks, 2008 financial crisis), the deep recession caused in the sector has led many experts to describe it as the worst in the entire history of commercial aviation, with noticeable effects on all study metrics. In addition to presenting the impact of the pandemic on the commercial aviation sector on a global scale, based on official data and statistics from the main industry organizations, the main objective of this work is to carry out an analysis of the air connectivity of the Spanish airports to understand and visualize the changes that have occurred in the country's airport network due to the COVID-19 pandemic. To do this, the degree of national structuring between urban systems (national connectivity) and the evolution of the participation of Spanish airports in the global scenario (international connectivity) in 1970, 2015, 2019 and 2020 (first post-pandemic summer) will be analyzed diachronically. , through the study of connectivity with a topological connectivity coefficient. The work closes with the conclusions of the investigation, presenting some of the initiatives undertaken by governments and aeronautical authorities to provide "certainty" in terms of health and safety in the world's airports, in order to rebuild trust in aviation. society in the short, medium and long term.